EcoEvo Icelandic Arctic charr population divergence ... - Brachmann, Matthew (Dryad, 2021)
Conceptual models of adaptive divergence and ecological speciation in sympatry predict differential resource use, phenotype-environment correlations, and reduced gene flow among diverging phenotypes. While these predictions have been assessed in past studies connections among them have rarely been assessed collectively. We examined relationships among phenotypic, ecological, and genetic variation in Arctic charr (Salvelinus alpinus) from six Icelandic localities that have undergone varying degrees of divergence into sympatric benthic and pelagic morphs. We characterized morphological variation with geometric morphometrics, tested for differential resource use between morphs using stable isotopes, and inferred the amount of gene flow from single nucleotide polymorphisms. Analysis of stable isotopic signatures indicated that sympatric morphs showed similar difference in resource use across populations, likely arising from the common utilization of niche space within each population. Carbon isotopic signature ... : We collected Arctic charr during morph specific spawning periods from Icelandic lakes and rivers using nordic gill nets varying in size. We identified each morph based on multiple phenotypic characteristics which are unique to each morphs within a population. We then took photographs for geometric morphometrics, measured body size, and took white muscle tissue for stable isotope and genotype analyses. ...